2000
DOI: 10.1143/jjap.39.5399
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PbTiO3/Pt/Yttria Stabilized ZrO2 Heteroepitaxial Films on Si Substrate

Abstract: Fabrication of PbTiO3/Pt/yttria-stabilized ZrO2(YSZ) heteroepitaxial films on Si substrate was investigated with the aim of applying them to electric devices such as integrated infrared sensors and ferroelectric random-access memories (FRAMs). First, a (100)YSZ buffer layer was epitaxially grown on a (100)Si substrate using reactive electron-beam evaporation. In this process, a metallic Zr film was deposited before YSZ deposition in order to prevent a Si substrate surface from oxidizing. Then, Pt film was sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…The cubic form of ZrO 2 thin films is usually stabilised by adding other oxides, typically Y 2 O 3 , but Sc 2 O 3 , 1 CaO, 2 CeO 2 , [3][4][5] In 2 O 3 , 6 Gd 2 O 3 , 7 MgO, 2,7 Al 2 O 3 1,8 and MgAlO 3 9 have also been used. YSZ has been used as a buffer layer for high-T c superconducting, [10][11][12] ferroelectric [13][14][15] and pyroelectric 16 films as well as for protective coatings on YBa 2 Cu 3 O 72d . 17 It has also been studied for field effect transistor (FET) type oxygen sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cubic form of ZrO 2 thin films is usually stabilised by adding other oxides, typically Y 2 O 3 , but Sc 2 O 3 , 1 CaO, 2 CeO 2 , [3][4][5] In 2 O 3 , 6 Gd 2 O 3 , 7 MgO, 2,7 Al 2 O 3 1,8 and MgAlO 3 9 have also been used. YSZ has been used as a buffer layer for high-T c superconducting, [10][11][12] ferroelectric [13][14][15] and pyroelectric 16 films as well as for protective coatings on YBa 2 Cu 3 O 72d . 17 It has also been studied for field effect transistor (FET) type oxygen sensors.…”
Section: Introductionmentioning
confidence: 99%
“…29 Both physical and chemical gas phase techniques as well as sol-gel 30,31 processes have been applied for the deposition of YSZ thin films. Physical vapor deposition methods such as electron beam evaporation, 15,32 sputtering [33][34][35] and pulsed laser deposition [36][37][38] have been frequently used. Chemical vapor deposition (CVD) methods include spray pyrolysis, [39][40][41] electrochemical vapor deposition 42 as well as conventional, 43 aerosol 44 and plasma assisted CVD.…”
Section: Introductionmentioning
confidence: 99%
“…They allow to distinguish between purely fibre textured layers, layers with several orientational variants and films with only one epitaxial texture component. As observed in former studies by other groups, (111)-oriented metal films are frequently composed of two or more texture components (twins) which are rotated azimuthally against each other [26,[30][31][32].…”
Section: Resultsmentioning
confidence: 53%
“…(111)-oriented metal films are still predominantly grown on oxide single crystals [21][22][23][24][25]. Attempts of Okamoto et al [26] and Tokita et al [27] to use YSZ/Si(0 0 1) as substrate for the growth of Pt(111) yielded films with four equivalent texture variants.…”
Section: Introductionmentioning
confidence: 99%
“…11) As a reference, their data are displayed in Table II. In addition, Lander and Morrison suggested that the reaction of 2Si + O 2 → 2SiO↑ (2) occurs in the Si etching region, which includes the condition of P B = 5 × 10 −7 Torr and T s = 700 • C. 23,24) The summation of 2 × (1) and (2) results in the following equation of…”
Section: Mechanism For Epitaxial Growth Of Sro On Simentioning
confidence: 99%